PKM PEMERIKSAAN TEKANAN DARAH DAN EDUKASI TENTANG HIPERTENSI DAN PENANGANANNYA DI DUSUN I DESA BUKIT KEMUNING KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Erma Kasumayanti; Maharani Maharani (COVIT (Community Service of Health), 2021)
Hypertension is a degenerative disease that is a serious problem today, hypertension can be triggered by lifestyle factors related to unhealthy eating patterns, smoking and lack of exercise, a family history of hypertension and can also be caused by stress factors. Most patients do not know they have hypertension even though they already feel the symptoms of hypertension. The lack of public awareness in controlling blood pressure and the lack of knowledge about hypertension and its treatment causes patients to experience repeated increases in blood pressure and even the occurrence of advanced complications. In Bukit kemuning village, most of the elderly have hypertension and some even experience some complications. Blood pressure checks and education about hypertension can help in knowing and controlling blood pressure as well as providing understanding in preventing or overcoming hypertension and providing awareness in implementing a healthy lifestyle so as to avoid hypertension. This activity starts from the preparation stage, the implementation of the activity. After conducting PKM on the elderly on June 29, 2021. It was found that the elderly knew blood pressure and increased their knowledge or understanding of hypertension and its management.